The effect of stop of mixing process during the anaerobic digestion process on both productivity and percentage of methane within the biogas mixture. - assaad, aziz (Latakia University Journal -Biological Sciences Series, 2022)
The rapid global population growth has caused an increase in the demand for various energy sources as a result of the increase in various human activities. The world began to work actively to rely on renewable energy sources to meet these requirements and to mitigate the negative environmental impacts of using non-renewable energy sources, of which anaerobic fermentation is one of these sources. This current study comes with the purpose of shedding light on the negative effects of the problem of stopping the mixing process during the anaerobic fermentation process on both the productivity of methane gas in addition to the percentage of methane gas within the resulting biogas mixture. This experiment was carried out on the farm of the University of UNI-LaSalle in France, within a 1m3 fermenter, which was fed with 15 kg of corn silage daily. The yield of the fermenter was 2±0.5 m3 of biogas per day. Where the results of the biogas mixture analysis showed that, the average productivity of methane was 1±0.26 m3 per day. The rates of productivity increase ranged from one stopping of mixing to another, where the rates of increasing productivity after returning from the stopping process during the three periods were as follows (170%, 45%, 100%) of these percentages, it is clear that stopping the mixing process has a significant impact on the productivity of the fermenter’s gas methane; Also, the percentage of methane gas within the biogas mixture decreased by 2-3% (during the mixing period) from the average productivity during the experiment.